Orofacial tuberculosis: clinic, diagnosis, differential diagnosis = Орофациальный туберкулез: клиника, диагностика, дифференциальная диагностика: - Tarasova, L. G. Lyudmila G. (Siberian State Medical University, 2020)
Current data on tuberculosis of orofacial localization are presented. Issues of etiology, classification, pathogenesis, risk factors, clinical features, diagnosis, differential diagnosis are disclosed. An algorithm is presented for examining patients with suspected orofacial tuberculosis and features of the treatment of the disease. In view of the rare localization of the disease, the training material is illustrated by the clinical data of patients with verified orofacial tuberculosis, which are publicly available and published on the Internet in specialized journals. Tests are presented in various modifications, the answers to situational tasks are oriented to practice, which completes the high-quality and complete development of the academic discipline. The manual has been developed for the work program of the module "Infectious Diseases, Phthisiology" in the phthisiology unit for the direction of preparation 05.31.03 - Dentistry for students of higher medical educational institutions and is recommended for use for independent preparation for classes and in-depth study of the material.